Second law considerations in fourier heat conduction of a lattice chain in relation to intermolecular potentials - Christopher, G.J. (2016)
Two aspects of conductive heat are focused here (i) the nature of conductive heat, defined as that form of energy that is transferred as a result of a temperature dierence and (ii) the nature of the intermolecular potentials that induces both thermal energy flow and the temperature profile at the steady state for a 1-D lattice chain. It is found that the standard presuppositions of people like Benofy and Quay (BQ) following Joseph Fourier do not obtain for at least a certain specified regime of intermolecular potential parameters related to harmonic (quadratic) potentials for nearest neighbor interactions. For these harmonic potentials, it appears from the simulation results that steady state solutions exist utilizing non-synthetic thermostats that couple not just the two particles at the extreme ends of the lattice chain, but to a control volume of N particles located at either ends of the chain that does not accord with the unique analytical solutions that obtains for single particle thermostatting at the ends of the lattice with a dierent thermostatting algorithm that utilizes coupling coecients. If the method used here is considered a more ”realistic” or feasible model of the physical reality, then a re-evaluation of some aspects of the standard theoretical methodology is warranted since the standard model solution profile does not accord with the simulation temperature profile determined here for this related model. We also note that the sinusoidal temperature profile generated suggests that thermal integrated circuits with several thermal P-N junctions may be constructed, opening a way to create more complex thermal transistor circuits. A stationary principle is proposed for regions that violate the Fourier principle Jq:rT 0, where Jq is the heat current vector and T the temperature.